(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The purpose of this study is to determine the conformity (verification) of the current model of tariff formation for gas distribution service of gas companies to the principle of incentive regulation based on the selection of model elements and their comparison with the world successful experience. The method of verification based on the selection of model elements, the determination of the advantages and disadvantages of such a model, and the comparison of the latter, introduced at domestic gas companies on natural gas distribution, with the world’s successful experience in regulating this issue. It is presented that this model does not fully comply with the principles based on long-term incentive regulation, which show its effectiveness in the world, which will be continued in the following studies.